Cardiac and Vascular Surgeons for the Treatment of Aortic Disease: A Successful Partnership for Decision-Making and Management of Complex Cases. (January 2021) - Capoccia, Massimo; Pal, Soumik; Murphy, Michael; Mireskandari, Maziar; Hoschtitzky, Andreas; Nienaber, Christoph A.; Cheshire, Nicholas J.; Rosendahl, Ulrich P.
Traditionally, cardiac and vascular surgeons have been treating diseases of the aorta as individual specialists. Neither cardiac nor vascular surgeons have ever considered the aorta as a whole, which can be diseased throughout its length at the same time requiring a more thoughtful and different approach. Aortic dissection and aneurysmal disease may well benefit from a multidisciplinary approach. In the context of this review, we discuss examples of joint operating between cardiac and vascular surgeons that may well become a more routine approach in more units in the future.